Dietary patterns and Helicobacter pylori infection in a group of Chinese adults ages between 45 and 59 years old: An observational study. Issue 2 (January 2019) - Shu, Long; Zheng, Pei-Fen; Zhang, Xiao-Yan; Feng, Yu-Liang
Abstract : Abstract: Limited studies have reported the association between dietary patterns and the risk of Helicobacter pylori ( H pylori ) infection. The purpose of this study was to evaluate the relationship between dietary patterns and H pylori infection in a Chinese population ages from 45 to 59 years. We performed a cross-sectional examination of the associations between dietary patterns and H pylori infection in 3014 Chinese adults ages between 45 and 59 years from Hangzhou city, Zhejiang province, China. Dietary intake was assessed through a semi-quantitative food frequency questionnaire (FFQ). H pylori infection was diagnosed using the 13 C-urea breath test. Multivariable logistic regression analyses were used to determine the associations between dietary patterns and the risk of H pylori infection. The prevalence of H pylori infection was 27.5%. Four major dietary patterns were identified by means of factor analysis: health-conscious, Western, grains-vegetables and high-salt patterns. After adjustment for the potential confounders, participants in the highest quartile of the "grains-vegetables" pattern scores had a lower odds ratio (OR) for H pylori infection (OR = 0.82; 95% confidence interval [CI]: 0.732–0.973; P  = .04) than did those in the lowest quartile. Compared with those in the lowest quartile, participants in the highest quartile of the "high-salt" pattern scores had a greater OR for H pylori infection (OR = 1.13; 95%CI: 1.004–1.139; P  = .048). Besides, no significant associations were found between the "health-conscious" and "Western" dietary patterns and the risk of H pylori infection. Our findings demonstrate that the "grains-vegetables" pattern is associated with a decreased risk, while "high-salt" pattern is associated with an increased risk of H pylori infection.